Power and the Land - Ivens, Joris; Crosby, Floyd; Ornitz, Arthur J. (image Entertainment, 1999)
This historically important documentary tells the story of the Parkinson family, farmers in rural Ohio who electrified their farm with the help of a Rural Electrification Administration loan. [www.amazon.com]